2012
DOI: 10.1002/bmc.2838
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of zeylenone in rat plasma by the presence of esterase inhibitors and its LC‐MS/MS assay for pharmacokinetic study

Abstract: Six esterase inhibitors, namely EDTA·2Na(+), NaF, phenylmethanesulfonyl fluoride, dichlorvos, bis-nitrophenyl phosphate (BNPP) and thenoyltrifluoroacetone, and the mixture of NaF and BNPP, were evaluated for the stabilization of labile benzoate containing zeylenone in rat plasma. The mixture appeared to exhibit the most effectively stabilizing effect with the degraded content of zeylenone decreasing from >60% (in the absence of inhibitors) to <6%. Following the stabilization by the addition of NaF (5 mM) and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The plasma sample was then mixed with formic acid which inhibited enzymatic reactions. We have tested different types of non-toxic esterase inhibitors at concentrations higher than other reports ( Wei et al, 2013 ; Cai et al, 2018 ; Bhuket et al, 2019 ) by 3–30 folds. We used BNPP and dichlorvos, carboxylesterase inhibitors; TLCK, serine hydrolase inhibitors; Pefabloc, carboxylesterase and serine hydrolase inhibitor; NaF, non-specific inhibitor ( Bhuket et al, 2019 ), but none of them were comparable with formic acid in inhibitory efficiency and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma sample was then mixed with formic acid which inhibited enzymatic reactions. We have tested different types of non-toxic esterase inhibitors at concentrations higher than other reports ( Wei et al, 2013 ; Cai et al, 2018 ; Bhuket et al, 2019 ) by 3–30 folds. We used BNPP and dichlorvos, carboxylesterase inhibitors; TLCK, serine hydrolase inhibitors; Pefabloc, carboxylesterase and serine hydrolase inhibitor; NaF, non-specific inhibitor ( Bhuket et al, 2019 ), but none of them were comparable with formic acid in inhibitory efficiency and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…The continuous metastasis and proliferation of PCa cells are important clinical features and a principal cause of mortality in the advanced stage of this cancer ( 22 , 23 ). It was demonstrated that Zey demonstrates cytotoxicity to tumor cells ( 10 , 24 ). Similar to previous studies ( 8 , 9 ), the present study demonstrated that Zey decreased the viability of DU145 cells.…”
Section: Discussionmentioning
confidence: 99%